Competence-based vocational and professional education : bridging the worlds of work and education - Mulder, Martin [Herausgeber] (Springer International Publishing, 2017)
"This book presents a comprehensive overview of extant literature on competence-based vocational and professional education since the introduction of the competence concept in the 1950s. To structure the field, the book distinguishes between three approaches to defining competence, based on: (1) functional behaviourism; (2) integrated occupationalism; and (3) situated professionalism. It also distinguishes between two ways of operationalizing competence: (1) behaviour-oriented generic, and (2) task-oriented specific competence. Lastly, it identifies three kinds of competencies, related to: (1) specific activities, (2) known jobs, and (3) the unknown future. The book presents a range of different approaches to competence-based education, and demonstrates that competence-based education is a worldwide innovation, which is institutionalized in various ways. It presents the major theories and policies, specific components of educational systems, such as recognition, accreditation, modelling and assessment, and developments in discipline-oriented and transversal competence domains. The book concludes by synthesizing the different perspectives with the intention to contribute to further improving vocational and professional education policy and practice." (Publisher, BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; L 6.2.1 Standards/Gütekriterien; I 2.3.2 Nordamerika; I 2.2 Europa; I 2.3.4 Asien; Bildungspolitik; Kompetenzbegriff; Kompetenzorientierung; Kompetenzbewertung; Internationaler Vergleich; Amerika; Europa; Asien